High frequency amplification of acoustic phonons in fluorine-doped single-walled carbon nanotubes - Sekyi-Arthur, D.; Mensah, S.Y.; Amewode, .K.; Jebuni-Adanu, C.; Asare, J. (Diamond & Related Materials, 2024)
Herein, we report on a strong high-frequency induced amplification of coherent acoustic phonons in a non degenerate fluorine-doped single-walled carbon nanotubes (FSWCNTs) by utilising a tractable analytical approach in the hypersound regime, ql≫1 (where q is the acoustic wavenumber and l is the carrier mean free path). The acoustoelectric gain obtained is highly nonlinear and is due to stimulated Cerenkov phonon emission by electrically driven carriers undergoing intraminiband transport and capable of performing Bloch oscillations. The transport process causes the carriers to undergo population inversion leading to intraminiband phonon assisted processes. The generation rate (phonon emission) is expansive and surpasses phonon losses. The threshold field (Eo), at which attenuation switches over to amplification (gain) depends on the FSWCNT pa rameters (Δs&Δz), carrier drift velocity (vd = μEo), sound velocity (vs) and the ratio ζs,z. This result has potential for intense sources of reasonable acoustic phonons in the sub-THz regime and is vital for the generation of SASER (sound amplification by stimulated emission of acoustic radiation). The amplified phonons also have THz fre quencies with wavelengths in the nanometer range, and depends on high spatial parameters which has potential applications for phonon filters and spectrometers.
Research Article
Keywords: Carbon nanotube; Fluorine; Cerenkov